ANALISIS HUKUM PENYERTAAN “DELLNEMING” DALAM PENEGAKAN HUKUM PIDANA PEMILU : EVALUASI PEMILU 2019 DAN PROYEKSI PEMILU 2024 - Kurnia, Yusup (Jurnal Keadilan Pemilu, 2021)
The general elections and elections in 2024 will be the first experiences because they will be held concurrently in the same year. Reflecting on the implementation of the 2019 elections, the Integrated Law Enforcement Center's (Gakkumdu) discussion of problems has a significant impact on the process of enforcing the Election Criminal Law. The issue stems from the process of completing the elements of election crime. Substantive law enforcement is important to put forward, considering that, empirically, in the 2019 elections, it has produced a precedent in the application of the "deelneming" articles of inclusion. This is evident from the analysis of the tendency of decisions by judges who handed down guilty verdicts in cases involving the application of the inclusion article elements (deelneming). One of the Election Supervisory Agency's (Bawaslu) top priorities as they prepare for the 2024 General Election is to strengthen the Integrated Law Enforcement Center (Gakkumdu). The Election Supervisory Agency (Bawaslu) makes breakthroughs in optimizing the enforcement of election criminal law as one of the elements in the Gakkumdu center, alongside the police and the prosecutor's office. One aspect is related to conducting scientific studies and increasing HR capacity in the process of enforcing election criminal law.